Thyroid functions in patients with hypochondriasis - Namli, Mustafa Nuray; Baykara, Sema; Atmaca, Murad (Kare Publ, 2022)
OBJECTIVE: No studies of thyroid-related hormone levels have been conducted in patients with hypochondriasis to date. The aim of this study is to examine thyroid-related hormones in patients with hypochondriasis.METHODS: Sixty patients with hypochondriasis and 138 healthy controls were included in this study. Patients with hypochondriasis who applied to the psychiatry outpatient clinic and met the study criteria and healthy controls were determined by chart analysis.RESULTS: According to the results of the comparisons, TSH, fT3, and fT4 levels did not show a statistically significant difference between hypochondriasis patients and healthy controls.CONCLUSION: Thyroid hormone levels are not associated with hypochondriasis.
Keywords: FT3; FT4; hypochondriasis; TSH